Role of optimization algorithms based fuzzy controller in achieving induction motor performance enhancement - Hannan M.A.; Ali J.A.; Hossain Lipu M.S.; Mohamed A.; Ker P.J.; Indra Mahlia T.M.; Mansor M.; Hussain A.; Muttaqi K.M.; Dong Z.Y. (Nature Research, 2023)
accuracy assessment; algorithm; control system; experimental study; instrumentation; optimization; performance assessment; simulation; algorithm; article; fuzzy logic; lightning; motor performance; simulation; velocity